1970
DOI: 10.3126/eco.v16i0.3464
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Population of Avifauna of Two Urban Sites in Dhaka, Bangladesh

Abstract: A comparative study on diversity and population status of avifauna in Uttara urban area of Dhaka city with their breeding records was done in 12-months period from August 2004 to July 2005. A total of 27 species of birds were recorded from two urban sites (Sectors 7 and 9). Species diversity was significantly more in Sector 7 than that recorded in Sector 9. Regarding the relative abundance, the highest number of species of birds (44%) was very common in Sector 7. In contrast, the number of rare species (33.33%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…The survey was carried out in January 2018 (winter season) and April 2018 (spring season). Fixed Radius Point Count method (Sarkar et al 2009) was used and altogether 28 plots were established at four different sites (bus park area, mine area, community forest area and Botanical Garden area). Selection of sites was based upon the forest types and habitats.…”
Section: Methodsmentioning
confidence: 99%
“…The survey was carried out in January 2018 (winter season) and April 2018 (spring season). Fixed Radius Point Count method (Sarkar et al 2009) was used and altogether 28 plots were established at four different sites (bus park area, mine area, community forest area and Botanical Garden area). Selection of sites was based upon the forest types and habitats.…”
Section: Methodsmentioning
confidence: 99%
“…Among the total observed wildlife, amphibians were 6.50% (8 species), reptilians 10.57% (13 species), birds 68.29% (84 species) and mammals were 14.64% (18 species) (Table 1). Sarker et al (2009) recorded 27 species of birds from two urban sites of Uttara, Dhaka. Rahman et al (2013) reported 89 species of wild animals of which, six (6.74%) species were amphibians, 11 (12.36%) reptiles, 56 (62.93%) birds and 16 (17.94%) mammals from Sirajgonj, Bangladesh.…”
Section: Species Richness Abundance and Densitymentioning
confidence: 99%
“…Das (1975) recorded 37 types of winged animals in Ramna Park. 19 watched an aggregate of 27 types of flying creatures from two unique locales in Dhaka, Bangladesh. A sum of 50 types of avifauna was found from Dhaka University.…”
Section: Supporting Servicesmentioning
confidence: 99%